Marvell, Spenser, and Civil War Epic in Upon Appleton House. - Cheney, Patrick (Review of English Studies, 2025)
In Upon Appleton House , Marvell imitates Spenser's Faerie Queene to turn a country house poem of political retirement into a mini-national epic. Marvell invents his model of epic retirement as a form of leadership at a challenging time in England's history. For Marvell's employer, Thomas Fairfax, had resigned his command of the Parliamentary forces during the Second Civil War, devoting himself to managing his Nun Appleton estate. During Marvell's residence at Nun Appleton, he turns his poetry of retirement into an epic enterprise through an imitatio of Spenser that is more deep-seated than criticism allows. Rather than writing an epic along the lines of The Faerie Queene , Marvell composes Upon Appleton House as an English Renaissance epic in the lyric key of a country house poem. To accomplish this generic feat, he innovatively presents retirement as an epic action. Spenser is instrumental to Marvell's meditation upon an epic poetry of retirement that places a country-house garden at its centre.